STRATEGIC POSITIONING OF RURAL TOURISM ON STARA PLANINA - Petrović, Gordana; Maksimović, Mlađan; Karabašević, Darjan (Economics of Agriculture, 2018)
Stara Planina has excellent potential for rural tourism development which might be encountered in a small number of mountains in our country. Stara Planina possesses rich biological, geological and cultural heritage. Achieving visible economic effects requires set of activities, support and continuous monitoring of all government levels. By providing tourist services to domestic and foreign tourists, signifcant proft is made. Positive result realization of tourism economy depends on its ability to satisfy visitors needs in the chosen tourism destination. Hence, the aim of this paper is to introduce the strategic positioning of rural tourism as important activity in the feld of tourism. In order to develop tourism in the best possible way, it is necessary to grasp the importance of strong economic growth of rural areas, so this paper thoroughly studies the respondents opinion on the basis of ANOVA method and it tries to highlight the strategic directions of rural tourism development on Stara Planina.